2022
DOI: 10.1186/s13012-022-01199-3
|View full text |Cite
|
Sign up to set email alerts
|

Do providers use computerized clinical decision support systems? A systematic review and meta-regression of clinical decision support uptake

Abstract: Background Computerized clinical decision support systems (CDSSs) are a promising knowledge translation tool, but often fail to meaningfully influence the outcomes they target. Low CDSS provider uptake is a potential contributor to this problem but has not been systematically studied. The objective of this systematic review and meta-regression was to determine reported CDSS uptake and identify which CDSS features may influence uptake. Methods Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 47 publications
1
51
1
Order By: Relevance
“…The fact that the design of the AdAM study included an underlying process evaluation that had been planned and published beforehand, improves the methodological quality of the trial. Furthermore, this process evaluation addresses each step of the CDSS application process and responds to the urgent need for a deeper understanding of CDSS uptake reported in a recently published systematic review [40]. We could show that GPs attached more importance to severe alerts, and that alerts relating to medication dosage and kidney function were more frequently dealt with than those concerning e.g., drug-drug interactions or possible unsuitability due to a patient's age (Intervention Dose).…”
Section: Strengths and Limitationsmentioning
confidence: 83%
“…The fact that the design of the AdAM study included an underlying process evaluation that had been planned and published beforehand, improves the methodological quality of the trial. Furthermore, this process evaluation addresses each step of the CDSS application process and responds to the urgent need for a deeper understanding of CDSS uptake reported in a recently published systematic review [40]. We could show that GPs attached more importance to severe alerts, and that alerts relating to medication dosage and kidney function were more frequently dealt with than those concerning e.g., drug-drug interactions or possible unsuitability due to a patient's age (Intervention Dose).…”
Section: Strengths and Limitationsmentioning
confidence: 83%
“…However, meta-analyses of CDS intervention studies show substantial heterogeneity in effect sizes [ 8 10 ]. Furthermore, widespread adoption of CDS systems has not been achieved [ 13 ], and access to CDS does not guarantee user uptake or acceptance in clinical settings [ 14 16 ]. For example, a review of 23 studies examining medication CDS systems found that between 46 and 96% of medication alerts were overridden by clinicians [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 159 , 160 In CDS studies, varying effect sizes can be due to inconsistent CDS uptake despite availability of the intervention. 161 …”
Section: Discussionmentioning
confidence: 99%